Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia - Khalloufi , Noureddine; Béjaoui, Mustapha; Delicado, Diana (European Journal of Taxonomy, 2020)
The aquatic biodiversity of springs and groundwater systems of North Africa remains largely unexplored. In an earlier field survey of Tunisian springs, a new gastropod genus, Bullaregia, was discovered as a phylogenetically independent lineage of uncertain position within the family Hydrobiidae. Here, we provide taxonomic and phylogenetic assignments for three newly collected populations of hydrobiids from springs in northern Tunisia based on morphological, anatomical and genetic (mtCOI and 18S) data. Among these and specimens of Bullaregia, major differences were observed in male and female genitalia as well as in mtCOI sequences (divergence 8.0–9.1%). Based on these findings, we describe two new genera and three new species: Belgrandiellopsis chorfensis gen. et sp. nov., Belgrandiellopsis secunda gen. et sp. nov. and Biserta putealis gen. et sp. nov. In all our phylogenetic analyses, these three new species were well resolved as a monophyletic group together with Bullaregia tunisiensis. Unexpectedly, this clade emerged as sister to the European valvatiform genera Corbellaria and Kerkia and not to the recently discovered clade of groundwater, conchologically similar, species living in Bulgaria (Balkan Peninsula). These Tunisian species are each locally endemic and form part of a newly discovered clade which in future systematic studies could eventually be identified as a distinct hydrobiid subfamily.